2021
DOI: 10.3390/jcm10112373
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Density Loss of the Deep Peripapillary Area in Glaucoma Suspects and Its Association with Features of the Lamina Cribrosa

Abstract: Purpose: To investigate the association of decreased vessel density (VD) in the deep peripapillary region and structural features of the lamina cribrosa (LC). Materials and Methods: 70 eyes of glaucoma suspects with enlarged cup-to-disc ratio were scanned and 51 eyes with adequate image quality were included in this study. All subjects had localized VD defects in the deep layer but intact VD in the superficial layer around the peripapillary region using optical coherence tomography angiography (OCTA). Only sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…LC thinning has also been associated with large CDRs and decreased vessel density in glaucoma suspects [ 32 , 33 , 34 ]. LC parameters such as cup depth, LC depth, prelaminar tissue thickness, and LC curvature index were associated with higher IOPs and thinner nerve fiber layers [ 35 ], as well as with a faster rate of RNFL loss [ 36 ]. Depth variations in the cup floor also differed between groups of normal subjects and glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…LC thinning has also been associated with large CDRs and decreased vessel density in glaucoma suspects [ 32 , 33 , 34 ]. LC parameters such as cup depth, LC depth, prelaminar tissue thickness, and LC curvature index were associated with higher IOPs and thinner nerve fiber layers [ 35 ], as well as with a faster rate of RNFL loss [ 36 ]. Depth variations in the cup floor also differed between groups of normal subjects and glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Although NFL and superficial retinal vessels are located in the retinal RNFL, no study has correlated NFL schisis and FA leakage in ERM with visual prognosis after vitrectomy. 10 Therefore, in this study, we evaluated the relationship between macular fluorescein leakage and RNFL schisis as visual prognostic factors for ERM. We also compared preoperative best-corrected visual acuity (BCVA), postoperative BCVA, and the degree of improvement in BCVA between the groups with or without macular fluorescein leakage and RNFL schisis.…”
mentioning
confidence: 99%
“…Jeon et al [ 20 ] showed clinical research results on “Vessel Density Loss of the Deep Peripapillary Area in Glaucoma Suspects and Its Association with Features of the Lamina Cribrosa”. These authors found that glaucoma suspects, with eyes having vessel density defects in the peripapillary area also displayed structural differences in the lamina cribrosa.…”
mentioning
confidence: 99%